Monitoring Suhu Dan Kelembapan Lahan Gambut Menggunakan Konsep Internet Of Things (IoT) - Yostisel Oktaria; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Internet of Things (IoT) is a new concept compared to cloud computing. Android applications or websites are used to monitor and control a network of electronic circuits and sensors throughsoftware designed for special purposes without human intervention to control it. With the development of current technology, environmental monitoring has also used the internet of things,including monitoring peatlands. When entering the dry season, peatlands will be vulnerable to land fires. In this study peatland monitoring with the concept of internet of things will facilitatelandowners, landowners or government companies to monitor peatlands. This research will monitor the temperature and humidity above and below the peatlands by using the DHT11 Temperature &Humidity sensor as input, Arduino as a microcontroller, Espressive Smart Connectivity Platform (ESP) as a WI-FI module to connect Arduino to the internet, internet platform of things usingANTARES to display the results of temperature monitoring and peatland humidity.Keywords: android, humidity, Internet of Things (IoT), monitoring, temperature